Phenolic composition of Anchusa undulataÂ L. subsp. hybrida (Ten.) Coutinho from Turkey - Abdurrahman Aktumsek, Gokhan Zengin, Cengiz Sarikurkcu (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Phenolic compounds are a major class of plant secondary metabolites. These compounds represent an important component of human diets and exhibit a wide range of biological effects, including antioxidant, anti-mutagenic, and anti-carcinogenic. To date, no study has been reported on the phenolic composition of Anchusa undulata subsp. hybrida. In this study, the phenolic constituents from the methanolic extract of A. undulata subsp. hybrida were analyzed by high-performance liquid chromatography-diode array detector. Thirteen compounds were identified. The major components include rosmarinic acid, benzoic acid, and rutin. Present study showed that A. undulata subsp. hybrida can be considered as good source of these components for food and drug applications.